A new variety of Brachystemma calycinum (Caryophyllaceae) from West Bengal, India with notes on its typification - Kumar, Anant (Phytotaxa, 2023)
Brachystemma (Caryophyllaceae) is an asian monotypic genus including B. calycinum. As part of field survey in Dooars and Darjeeling–Sikkim Himalaya (India), a population ascribed to this species was found. Since the different morphology, a new variety has been described and illustrated. Moreover, the typification of the name B. calycinum is also discussed.